2012
DOI: 10.1891/1946-6560.3.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Intimate Partner Violence Perpetration, Victimization, and Mental Health Among Women Arrested for Domestic Violence

Abstract: Intimate partner violence (IPV) is a major problem. Unfortunately there is a dearth of research on the associations between IPV perpetration, victimization, and mental health among women. The current study examined these associations among a sample of women arrested for domestic violence and court-referred to batterer intervention programs (BIPs; N = 88). Using self-report screening instruments for Axis I and Axis II mental health problems, results showed very high rates of mental health problems among women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 56 publications
3
29
1
1
Order By: Relevance
“…It is notable, though, that total BPD features were only uniquely associated with physical aggression, but not attitudinal or verbal aggression, when accounting for relevant demographic and clinical control variables. This is counter to some previous research demonstrating BPD features to be associated with various indicators of aggression in different populations (Ross & Babcock, 2009; Shorey et al, 2012). It is possible that ASPD features are a better predictor of aggression than BPD features among young adult men in substance use treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…It is notable, though, that total BPD features were only uniquely associated with physical aggression, but not attitudinal or verbal aggression, when accounting for relevant demographic and clinical control variables. This is counter to some previous research demonstrating BPD features to be associated with various indicators of aggression in different populations (Ross & Babcock, 2009; Shorey et al, 2012). It is possible that ASPD features are a better predictor of aggression than BPD features among young adult men in substance use treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Substance abuse has been positively (although not necessarily significantly) associated with IPV recidivism among both male and female offenders (e.g., Busch & Rosenberg, 2004;Henning et al, 2009;Ménard et al, 2009) and reductions in alcohol use following treatment have also been shown to reduce the occurrence of partner assaults by both men and women (e.g., Schumm, O'Farrell, Murphy, & Fals-Stewart, 2009). Simmons, Lehmann, and Cobb (2008), however, noted the inconsistencies in the literature with respect to the prevalence and predictive effects of substance abuse among female IPV offenders. They suggested that substance abuse is higher in convicted and treated samples and that it might actually contribute to decisions to convict and send women to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They are less likely to have criminal histories, including fewer custodial sentences, violations of conditional release, and prior offenses of any kind (e.g., Henning & Feder, 2004;Lake & Stanford, 2011;Moser, 2012). They also appear less likely to abuse drugs and alcohol (Friend, Langhinrichsen-Rohling, & Eichold, 2011;Gass, Stein, Williams, & Seedat, 2011), although this finding has been inconsistent (e.g., Busch & Rosenberg, 2004;Henning et al, 2009;Moser, 2012;Simmons, Lehmann, & Cobb, 2008;Stuart et al, 2008). Henning and Feder (2004) examined potential predictors of IPV recidivism in a sample of adults (17% women) arrested for IPV.…”
mentioning
confidence: 99%
“…It is possible that partners with history of mental and psychological disorders act more as the perpetrator of the IPV. Previous studies showed that both IPV perpetration and victimization were associated with increased mental health symptoms in males and females (Fulu et al, 2013;Shorey et al, 2012).…”
Section: Introductionmentioning
confidence: 96%